2014
DOI: 10.1021/jf5013538
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Ratio Analysis for Verifying the Authenticity of Balsamic and Wine Vinegar

Abstract: In this paper, we investigate whether the analysis of stable isotope ratios D/H and ¹³C/¹²C in ethanol and acetic acid and of ¹⁸O/¹⁶O in water can be applied to the ingredients of "aceto balsamico di Modena IGP" (ABM) to evaluate their authenticity. We found that impurities in the extraction solution do not affect the ¹³C/¹²C of acetic acid and the D/H values of acetic acid are not affected under a composite NMR experiment. The standard deviation of repeatability and standard deviation of reproducibility are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
0
19
0
2
Order By: Relevance
“…For an ABM residue after acetic acid extraction, which can be assimilated to a must, this general reference can be adopted . The ABM product specifications allow the addition of up to 2% caramel for colour stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For an ABM residue after acetic acid extraction, which can be assimilated to a must, this general reference can be adopted . The ABM product specifications allow the addition of up to 2% caramel for colour stability.…”
Section: Resultsmentioning
confidence: 99%
“…International Organization of Vine and Wine (OIV) methods are currently adopted: OIV‐MA‐AS311‐05 for site‐specific analysis of the D/H ratio using 2 H‐SNIF‐NMR ( 2 H‐site‐specific natural isotope fractionation–nuclear magnetic resonance [NMR]) and OIV‐MA‐AS312‐07 for analysis of the 13 C/ 12 C ratio (expressed as δ 13 C ‰) using isotope ratio mass spectrometry (IRMS). As demonstrated by Perini et al, these methods can also be effectively applied to ABM ingredients, including must . The limits for D/H and δ 13 C isotopic ratios are those in the official wine databank, when the origin and year of production are declared, or the more general limits reported in Dordevic et al…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies performed in relation to irm-2 H NMR demonstrated the feasibility of such an in situ method, 28 and it is used for current analyses of vinegars. 29 Thus, it has been demonstrated that the mass/purity ratio K′ of both standard and compound (eq 2) is equal to ratio K (eq 3), corresponding to the concentration ratio obtained by 1 H NMR,…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Pages et al [238] identified and quantified adulterants in sexual enhancement and weight loss dietary supplements (DS) with a benchtop cryogen-free low-field 1 H NMR spectrometer. To control the authenticity of vinegar [206][207][208] and rice spirits [203], a method named SNIF (sitespecific natural isotope fractionation)-NMR has been proposed to monitor adulteration. SNIF-NMR can distinguish acetic acid or ethyl alcohol from different raw materials on the basis of significant differences in the sitespecific ratio of deuterium to hydrogen.…”
Section: Food Analysismentioning
confidence: 99%